Analisis Perubahan Keputusan Pemerintah Maladewa Terhadap Kontrak Konsesi Bandara Internasional Male Dari Perusahaan GMR India Ke BUCG Tiongkok Pada Tahun 2010-2014 - Hasyaimi, Margi A. (Global and Policy Journal of International Relations, 2016)
ABSTRACTThis research aimed to analyze the changes of the Maldives government's decision on the cancellation agreement with GMR India and switch to cooperate with BUCG China. In 2010, the government of the Maldives signed a privatization agreement with the GMR-MAHB that produce concessions on Male International Airport. Two years after the signing of the agreement, airport operations under GMR caused controversy which led to the cancellation of the contract unilaterally by the government of Maldives. This study analyzes the changes in the Maldivian government's decision by rational choice theory, which states as rational actors will make decisions based on profit and loss, as well as the bandwagoning theory for profit as Maldives’s strategy for cooperation with China. Overall, the analysis of this study aimed to answer the hypothesis the changes of Maldives foreign policy was influenced by interest in the Maldives to join in the plan of 21st Century Maritime Silk Route of China.Keywords: privatization, consession, rational choice, bandwagoning for profit, 21st Century Maritime Silk RouteDOI : https://doi.org/10.33005/jgp.v4i02.1919